DIRECTIVE SPEECH ACTS FOUND IN UTTERANCES OF “THE HUSTLE” - Natalia Rebong; Ambalegin Ambalegin (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This research investigated the kinds of directive acts found in “The Hustle” movie. Descriptive qualitative was adopted as the research design of this research. All data were collected through observational method and non-participatory technique. The researchers analyzed the data by applying pragmatic identity method and pragmatic competence- in equalizing technique. The collected data were identified in pragmatics way by involving elements of pragmatics, namely speaker, interlocutor, and context to get the implied meaning. Then, the data were equalized with the theory of directive acts kinds developed by Kreidler (1998). The result of this research found out all types appeared in the movie as there had 39 data of request, 13 data of suggestion, and six data of command. Request became the most frequent kind in the utterances of the characters. The reason is that the characters commonly did not attempt to fully control the characters in order to get the action done.